THE IMPLEMENTATION OF GOVERNANCE AT THE GUNUNG GAMBIR RUBBER PLANTATION, PTPN NUSANTARA 1 REGIONAL 5: AN ISLAMIC PERSPECTIVE OF KALIGLAGAH VILLAGE, SUMBERBARU DISTRICT, JEMBER REGENCY - Siti Nur Fadilah; Mahmudah, Siti Masrohatin (CV. Adiba Aisha Amira, 2024)
The purpose of this study is aligned with its research focus, which includes: 1) To describe the implementation of governance through transparency at the Gunung Gambir rubber plantation of PTPN Nusantara 1 Regional 5 in Kaliglagah Village, Sumberbaru District, Jember Regency. 2) To describe the implementation of governance through accountability at the same plantation. 3) To describe the implementation of governance through responsibility at the Gunung Gambir rubber plantation. 4) To describe the implementation of governance through fairness at the plantation. 5) To describe the implementation of governance through sustainability at the Gunung Gambir rubber plantation. 6) To describe governance from an Islamic perspective at the Gunung Gambir rubber plantation. This research uses a qualitative approach to generate descriptive data through written or spoken words, focusing on observable behavior and a holistic understanding of individuals and their environments. The study aims to construct and comprehend social realities through direct interaction with subjects, grounding theories in contextual and historical settings. Field research is employed, with data collected via non- participatory observation and semi-structured interviews at the Gunung Gambir rubber plantation in Kaliglagah Village, Jember Regency, managed by PTPN Nusantara. The study examines governance from an Islamic perspective, emphasizing transparency, accountability, responsibility, fairness, and sustainability. The Gunung Gambir Rubber Plantation applies transparent governance, emphasizing openness, accountability, and fairness in its operations. By adhering to Good Corporate Governance (GCG), it builds stakeholder trust through accurate reports, public Annual General Meetings (AGMs), and clear communication. Despite challenges, the plantation integrates responsible governance practices such as sustainability, stakeholder involvement, and Islamic values like honesty, trustworthiness, and effective communication. Recommendations for improvement include fostering transparency through an ESG team, ensuring accountability with structured reporting and third-party audits, and adopting sustainable practices. This approach enhances the company's reputation, strengthens local partnerships, and supports long-term growth and community welfare